X線ラインプロファイル解析と透過電子顕微鏡観察による強圧下冷間圧延された純鉄，Fe-0.3 mass%Si合金，Fe-0.3 mass%Al合金の再結晶に伴う転位組織変化の評価 - 冨田, 美穂; 米村, 光治; 坂本, 広明; 稲熊, 徹; 潮田, 浩作 (鉄と鋼, 2017)
The change in dislocation structure with recovery and recrystallization of 99.8% cold-rolled pure iron, Fe-0.3 mass%Al and Fe-0.3 mass%Si alloys was investigated by means of X-ray line profile analysis (XLPA) and TEM observation. In as-rolled samples of Fe-Al and Fe-Si alloys, the fraction of edge dislocation density increased in comparison with that in pure iron. In the early stage of recovery, dislocation densities with both edge and screw components remarkably decreased in pure iron, whereas in the Fe-Al and Fe-Si alloys, only the edge dislocation density distinctively decreased. This suggests that edge dislocations with relatively high density in as-rolled Fe-Si and Fe-Al alloys are easily annihilated by the climbing up motion of edge dislocations. In the late stage of recovery, the dislocation density of Fe-Si alloy did not decrease. No structural changes were observed by TEM which suggests that the recovery of Fe-Si alloy is strongly retarded, since Si hinders dislocation movement. In the early stage of recrystallization of pure iron, the formation of large subgrains was clearly confirmed in the lamellar structure. The subgrains show a similar orientation to the neighboring unrecrystallized grains, which represents similar behavior regarded as continuous recrystallization. Fe-Al alloy is similar to pure iron. Whereas, Fe-Si alloy exhibits discontinuous recrystallization in the sense that grains with low dislocation density were confirmed in the unrecovered lamellar structure with high driving force for recrystallization. This is because the Si strongly hinders dislocation movement. This effect agrees with the behavior of dislocation in Fe-Si alloy confirmed by XLPA.